Start-ups: The Ladder towards a Developed and Innovative Economy, Opportunities and Vulnerabilities - Shunmugasundaram, V; Shivhare, Shivani (Nepalese Journal of Management Science and Research, 2023)
Start-up Entrepreneurship is crucial for the promotion of research, innovative systems, and self-employment. Entrepreneurs with high potential and calibre are scarce and precious human resources for the country. This paper examines the role played by the Indian start-ups for innovation and economic development, opportunities, and challenges considering start up survival. This research is descriptive in nature, we have studied the need, significance, and impact of start-ups on economic and innovation development, and also will investigate the causes and obstacles of the start-ups in India. Our analysis uses statistical techniques to examine the start-ups as the major success factor for an entrepreneur in India. We have evaluated the positive impact of start-ups on the economic and innovation development of the nation. There were larger policy implications for the promotion of this important sector. Start-ups are basically open organizations, certainly engaged in innovation processes. Research at the intersection between start-ups, innovation, and economic development is in demand. This paper attempt to organize the scientific knowledge related to the intersection between start-ups and innovation and economic development systematically.